THE INFLUENCE OF MACRO ENVIRONMENTAL FACTORS ON THE DEVELOPMENT OF FREE ECONOMIC ZONES - Maxsudov Sherzod Solijonovich (Scholars Digest Publishing, 2023)
Promotion of free economic zones by foreign agents. The role of political factors in the establishment of free economic zones. The role of economic factors in the economic development of the country. Social and technological factors in free economic zones. Creation of new jobs in the area where free economic zones are established. Employment of the population. An increase in the standard of living.
Keywords: World market, Globalization scale, Free economic zones, Economic space, Economic privileges, Political factor, Economic factor, Social factor, Technological factor, Modernization, Unemployment and inflation, Export potential, Infrastructure.